Chain rule difficulties, due tomorrow!! 1. The problem statement, all variables and given/known data Find the derivative of y=e^square root of 1+tan(sinx) 2. Relevant equations chain rule: F'(x)=f'(g(x)) * g'(x) 3. The attempt at a solution I thought I had it and then while I was looking at other chain rules and started doubting my actual ability to sort out the chain rule... y=e^square root of 1+tan(sinx) y'=e^square root of 1+tan(sinx) *(1+tansinx)' y'=e^square root of 1+tan(sinx)* (0 +sec2sinx +cosx) Please help! My assignment is due tomorrow and I know there is something not quite right but I don't know why.